2020
DOI: 10.1177/0361198120913288
|View full text |Cite
|
Sign up to set email alerts
|

Divergence between Performance in the Field and Laboratory Test Results for Alkali-Silica Reaction

Abstract: The most common test methods used to evaluate alkali-silica reaction (ASR) are the concrete prism test (CPT) and the accelerated mortar bar test (AMBT). However, these tests were not found to be entirely reliable in predicting the performance of concrete under field conditions, especially when supplementary cementitious materials (SCMs) are used. Recently, two new test methods, the miniature concrete prism test (MCPT) and the concrete cylinder test (CCT), have been proposed but still need to be benchmarked wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In numerous studies, the results gained by applying different tests and standards to assess alkali reactivity of aggregates were compared and benchmarked against the behavior of structures in the field. [17,[32][33][34][35]73,74] Sources of reference for high-alkali cements and nonreactive aggregates were established for international and interlaboratory trials of accelerated tests. Contradictory results were carefully analyzed, and the methods have been continuously improved based on the resulting insights.…”
Section: Assessment Of Asr Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous studies, the results gained by applying different tests and standards to assess alkali reactivity of aggregates were compared and benchmarked against the behavior of structures in the field. [17,[32][33][34][35]73,74] Sources of reference for high-alkali cements and nonreactive aggregates were established for international and interlaboratory trials of accelerated tests. Contradictory results were carefully analyzed, and the methods have been continuously improved based on the resulting insights.…”
Section: Assessment Of Asr Riskmentioning
confidence: 99%
“…[31] Other studies of these expert committees set the frame for categorizing and harmonizing accelerated ASR testing methods, including detailed explanations of the advantages and drawbacks of different strategies. [8] Another important focus lies on the organization of round robin tests, and on the assemblage and overall evaluation of field tests [32][33][34][35] which are an indispensable tool for the calibration of accelerated tests, including the definition of limit values with respect to measured expansions.…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…The authors also concluded that the CPT method is the most reliable ASTM method available currently, and the use of AMBT is possible to determine the required minimum amount of SCM to control ASR expansion as there is a low risk of damaging expansion in the field when the combination of materials pass the AMBT performance criteria [60]. The miniature concrete prism test -MCPT (AASHTO T 380 [61]) is a newer test method, which is also of interest as the preliminary results regarding the prediction of the field performance show promising results in shorter duration (up to 84 days) when compared to the CPT method [62,63].…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…PSC of concrete is determined either through extraction or modeling approaches. However, the extraction of pore solution from paste/mortar/concrete requires a complicated procedure, contingent on the applied pressure and is thus usually limited to early ages ( 17 , 18 ). As for modeling approaches, the online NIST model ( 19 ) is widely used to estimate the PSC of concrete mixtures based on bulk oxide compositions of concrete ingredients.…”
mentioning
confidence: 99%
“…As for modeling approaches, the online NIST model ( 19 ) is widely used to estimate the PSC of concrete mixtures based on bulk oxide compositions of concrete ingredients. However, several studies ( 18 , 20 ) have noted that while the NIST model provides a reasonable estimation of PSC for OPC mixtures, it significantly overestimates the PSC of fly ash mixtures, especially in cases of Class F FA ( 21 ). Of late, several researchers have successfully used the thermodynamic modeling approach to model hydration phase assemblage and predict the PSC of binary and ternary concrete mixtures ( 2225 ).…”
mentioning
confidence: 99%